PHONOLOGICAL VARIATION OF PASAR KLIWON ARABIC DIALECT SURAKARTA - Arief Nur Rahman Al Aziiz; Muhammad Ridwan (Prasasti: Journal of Linguistics, 2019)
This article studies about sound variation sand sound change in Arabic dialect Pasar Kliwon. The data searching use observe (simak) and conversation (cakap) method. The technique of data searching is record (rekam) and register (catat). The data searching refers to question list from 120 swadesh vocabularies. Data analysis used padan method and depends on informan’s speech organ. The analysis research use sound change theory according to Crowley (1992) and Muslich (2012). The vowel sound in Arabic dialect Pasar Kliwon divided by two kinds: short vowel sound and long vowel sound. There are twenty sevenconsonant sounds and divided by seven kinds: plosive, fricative, affricative, liquid, voiced, voiceless, and velariation sound. The sound variation of semi-vowel is wawu and ya>’. The vowel sound change divided by four kinds: lenition, anaptycsis, apocope, metathesis. The consonant sound change divided by four kinds:  lenition, anaptycsis, apocope, and sincope.The diftong sound change is monoftongitation.